Between Tradition and Change: The Scottish Social Economy Sector at a Crossroad - Baglioni, Simone; Mazzei, Micaela (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2021)
This paper discusses the origins and motives behind the rich institutional and policy infrastructure that Scotland has developed in previous decades to support the social economy sector. Drawing on a large body of primary data collected through an EU funded project this paper reflects upon the effects of the economic and financial crisis, and how such changes may shed light on the future of the social economy in Scotland.